The effect of a locally tailored intervention on the uptake of preconception care in the Netherlands: a stepped-wedge cluster randomized trial (APROPOS-II study) - V. Y. F. Maas; M. Poels; E. Ista; L. F. Menge; K. L. H. E. Vanden Auweele; R. W. A. de Bie; D. J. de Smit; E. H. van Vliet-Lachotzki; A. Franx; M. P. H. Koster (BMC, 2022)
Abstract Background The preconception period provides a window of opportunity for interventions aiming to reduce unhealthy lifestyle behaviours and their negative effect on pregnancy outcomes. This study aimed to assess the effectiveness of a locally tailored preconception care (PCC) intervention in a hybrid-II effectiveness implementation design. Methods A stepped-wedge cluster randomized controlled trial was performed in four Dutch municipalities. The intervention contained a social marketing strategy aiming to improve the uptake (prospective parents) and the provision (healthcare providers) of PCC. Prospective parents participated by administering a questionnaire in early pregnancy recalling their preconceptional behaviours. Experiences of healthcare providers were also evaluated through questionnaires. The composite primary outcome was adherence to at least three out of four preconceptional lifestyle recommendations (early initiation of folic acid supplements, healthy nutrition, no smoking or alcohol use). Secondary outcomes were preconceptional lifestyle behaviour change, (online) reach of the intervention and improved knowledge among healthcare providers. Results A total of 850 women and 154 men participated in the control phase and 213 women and 39 men in the intervention phase. The composite primary outcome significantly improved among women participating in the municipality where the reach of the intervention was highest (Relative Risk (RR) 1.57 (95% Confidence Interval (CI) 1.11-2.22). Among women, vegetable intake had significantly improved in the intervention phase (RR 1.82 (95%CI 1.14-2.91)). The aimed online reach- and engagement rate of the intervention was achieved most of the time. Also, after the intervention, more healthcare providers were aware of PCC-risk factors (54.5% vs. 47.7%; p = 0.040) and more healthcare providers considered it easier to start a conversation about PCC (75.0% vs. 47.9%; p = 0.030). Conclusion The intervention showed some tentative positive effects on lifestyle behaviours among prospective parents. Primarily on vegetable intake and the knowledge and competence of healthcare providers. The results of this study contribute to the evidence regarding successfully implementing PCC-interventions to optimize the health of prospective parents and future generations. Trial registration Dutch Trial Register: NL7784 (Registered 06/06/2019).